PENGUATAN KETERAMPILAN MENGAJAR DALAM UPAYA PENINGKATAN HASIL BELAJAR SISWA - Nurdin Mansur (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2014)
Study activity will succeed effectively and efficient if conducted by teacher owning good qualification well as having and able to apply better various skill teach as teacher of a subject.Teaching skill visible above mentioned among other things at study planning, study execution and perform  the evaluation [of] result of learning. From various skill teach above mentioned owned by somebody learn in teaching, hence student will like to learn with the teacher assessed skillful in teaching, so that by itself can awaken the student to learn seriously, so that thereby student can reach for the result learn better also. That result learn high reached for   student in a  that subject  is interconnected once with the factor learn in hand and implementations the teaching skills in study, like skill open the lesson, skill enquire the, skill give the reinforcement, skill give the variation, skill explain the, skill guide the small group discussion, skill manage the class, skill teach the civil, and skill close the lesson. Others, in school activity of a  subject, student claimed to ready to execute the practice to enhance to feel the self confidence, willingness which ossify in applying various strategy and technique learn correct, planning and good self confidence to arrangement  so that  can reach of result learn high. Hence thereby, needed   by  student assessment which do well by the learning skill in teaching, high excelsior of student assessment to learning skill in teaching hence excelsior also result of learning reached for   a student. On the contrary progressively lower the student assessment to learning skill in teaching hence progressively lower also result of learning reached of student.